Educação para a diversidade : acervos complementares do PNLD/2010 - Amaral, Liliane Melo do (My University, 2014)
This dissertation analyses the representation of cultural identities in books of the human Science area, set 1 from complementary book collection PNLS 2010; aimed to the two first years of elementary school and the contribution or not of these titles to education for diversity. The question is based on the higher and higher insertion of children who come from distinct realities in the Scholar nets and because this material is present in in all Brazilian public schools, it should be problematized so that they do not become perpetual stereotypes and prejudice. The search is inserted in the Post - Graduation Program in Education of Caxias do Sul University – PPGEd/UCS, in the Education search , Languages and Technology and it is part of the research project ―Education, Language and Reading Practices II‖, having as a main topic, the study of cultural products distributed by the Education Ministery (MEC) to the public schools and its potentialities for an emancipatory and ethical education. The theoretical contribution of the dissertation is formed by Adorno (1995), Vigotski (2007, 2008, 2012), Dewey (1971), Larrosa (2002), Bakhtin (2003, 2010), Soares (2012, 2013), Fonseca (2009), Chartier (1991), Pesavento (2008), Platão (1991), Hall (1996, 1997,2006), Solé (1998), among others. The text is structured in three chapters: first – Education, Language and History teaching; second – Complementary Book Collection and Education for Diversity and third – Mediation of the works – didactic sequence proposals. The applied method in the study of the works is the analytical, doing the search initially and the theoretical research to build the theoretical board which based the post title analysis, which the objective is to analyze representations of cultural identities present in the corpus and in the end, propose, in an interactional perspective possibilities of mediation of the copies as subsidies to the teachers which act in the elementary school. This work had three works of the Human Science from the set 1 from the complementary book collection, such as : Kabá Darebu (2002), by Daniel Munduruku; Seis pequenos contos africanos sobre a criação do mundo e do homem (2009), by Raul Lody and A caminho da escola (2009) by Fábia Terni. It was concluded that Education for diversity is potentiated by the works from complementary book collection, they represent the cultural ethical identities and the mediation of the teacher is important to problematize them and guide the students in the comprehension on how they build their identities in relation to the others.
Esta dissertação analisa a representação de identidades culturais em obras da área de Ciências Humanas do conjunto 1 dos acervos complementares PNLD 2010, destinados aos dois primeiros anos do Ensino Fundamental, e a contribuição ou não destes títulos à educação para a diversidade. A questão fundamenta-se pela inserção cada vez maior de crianças com realidades distintas nas redes escolares e por esse material estar presente em todas as escolas públicas brasileiras, devendo ser problematizado para que não se perpetuem estereótipos e preconceitos. A pesquisa insere-se no Programa de Pós-graduação em Educação da Universidade de Caxias do Sul – PPGEd/UCS, na linha de pesquisa Educação, Linguagens e Tecnologia e é parte integrante do projeto de pesquisa ―Educação, Linguagem e Práticas Leitoras II‖, tendo como ponto principal o estudo de produtos culturais distribuídos pelo Ministério da Educação (MEC) às escolas públicas e suas potencialidades para uma educação emancipatória e ética. O aporte teórico da dissertação é formado por Adorno (1995), Vigotski (2007, 2008, 2012), Dewey (1971), Larrosa (2002), Bakhtin (2003, 2010), Soares (2012, 2013), Fonseca (2009), Chartier (1991), Pesavento (2008), Platão (1991), Hall (1996, 1997,2006), Solé (1998), entre outros. O texto está estruturado em três capítulos: primeiro – Educação, Linguagem e Ensino de História; segundo – Acervos complementares e a educação para a diversidade e terceiro – Mediação das obras – propostas de sequências didáticas. O método aplicado no estudo das obras é o analítico, realizando inicialmente a pesquisa teórica para a construção do quadro teórico que embasou a posterior análise dos títulos, que objetiva analisar representações de identidade cultural presentes no corpus e, ao final, propor, em uma perspectiva interacionista, possibilidades de mediação dos exemplares como subsídios aos docentes que atuam nos anos iniciais do Ensino Fundamental. A dissertação teve como objeto três obras da área de Ciências Humanas do conjunto 1 dos acervos complementares, sendo elas: Kabá Darebu (2002), de Daniel Munduruku; Seis pequenos contos africanos sobre a criação do mundo e do homem (2009), de Raul Lody e A caminho da escola (2009), de Fábia Terni. Conclui-se que a educação para a diversidade é potencializada pelas obras dos acervos complementares que representam as identidades culturais étnicas e a mediação do professor é importante para problematizá-las e orientar os alunos na compreensão de que constroem suas identidades na relação com os outros.
Keywords: Educação; Educação e Estado; História - Estudo e ensino; Ensino fundamental; Education; Education and State; History - Study and teaching